Gaspra - software for astronomical image processing in high-performance computing clusters (Revista Brasileira de Computação Aplicada, 2014)
There is a huge amount of information generated by telescopes as astronomical images. Therefore, software and equipment could process these images to find new phenomena and obtain new knowledge about the space. Considering the need of rapid processing of those images, we present a software for astronomical image processing in high-performance computing clusters, which use shared and distributed memory systems, called Gaspra. We designed Gaspra to batch process large sets of astronomical images, allowing researchers to create scientific workflows to obtain new knowledge from these astronomy imagery data sets. Experiments with Gaspra show a 3.5-fold speedup to process a single image in 5 processing nodes, each node supporting 64 different threads.